2009
DOI: 10.1037/a0015816
|View full text |Cite
|
Sign up to set email alerts
|

How much do I tell thee? Strategies for managing information to parents among American adolescents from Chinese, Mexican, and European backgrounds.

Abstract: Strategies for managing information about activities to parents, including partial disclosure, avoidance, lying, and full disclosure, were examined in 479 American adolescents (M = 16.38 years, SD = 0.77) varying in generational status and from Mexican, Chinese, and European backgrounds. Information management strategies for personal, prudential, and overlapping (multifaceted) activities as defined within social domain theory were examined. With age, parental education, and generational status controlled, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 47 publications
(96 reference statements)
3
42
0
5
Order By: Relevance
“…This pattern of deflecting attention from potentially contentious issues is consistent with the Japanese cultural emphasis on minimizing interpersonal conflicts (Markus & Lin, ) and maintaining interpersonal harmony within the family (Yamada, ). As has been found elsewhere (Tasopoulos‐Chan et al., ), avoiding the topic was used more frequently to manage information about prudential than multifaceted or personal issues and among boys more than girls, perhaps because it is easier to avert a conflict if the issue does not arise.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This pattern of deflecting attention from potentially contentious issues is consistent with the Japanese cultural emphasis on minimizing interpersonal conflicts (Markus & Lin, ) and maintaining interpersonal harmony within the family (Yamada, ). As has been found elsewhere (Tasopoulos‐Chan et al., ), avoiding the topic was used more frequently to manage information about prudential than multifaceted or personal issues and among boys more than girls, perhaps because it is easier to avert a conflict if the issue does not arise.…”
Section: Discussionmentioning
confidence: 64%
“…Adolescents selected the primary strategy they used for telling or not telling their parents about each issue. Based on previous research (Darling et al., ; Tasopoulos‐Chan, Smetana, & Yau, ), and verified using focus group responses, the strategies were: “Tell [parent] all the important details,” “Tell [parent] only when he/she asks,” “Avoid discussing the issue,” “Leave out important details [parent] wants to know,” and “Make up a story” (e.g., lie). As with justifications, separate proportion scores were created for each strategy, reflecting adolescents' use of a particular strategy for items in that domain relative to the total number of items in the domain.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents may view parents who have a history of engaging in receptive communication as more trustworthy (Tasopoulos-Chan, Smetana, & Yau, 2009), leading them to feel safer openly discussing past and current smoking behavior. We also examined in the present study potential heterogeneity among teens who used different concealing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research does provide some support for such a link. For example, using generational status as a proximal measure of acculturation, Tasopoulos-Chan et al (2009) found that second generation Chinese American youth more frequently avoided discussing their activities with their parents than did first generation Chinese American youth. In a case study of Chinese immigrant families, Qin (2006) found that both parents and children report that parents do not know about their children’s friends and school activities and children do not tell their parents about their experiences due to the fact that parents and children adhere to the heritage and mainstream cultures to different degrees.…”
Section: Introductionmentioning
confidence: 99%